Implementasi Nilai Nasionalisme dalam Pembelajaran Sejarah Materi Organisasi Pergerakan Nasional di Kelas XI MAN Sidoarjo - Anisah, Diana Fitri; Aziz, Muhammad Faris Abdil; Fajriyah, Izzatul (Jurnal Artefak, 2025)
The research aims to find out the process of planning and implementing nationalism values, as well as the obstacles faced in implementing nationalism values in history learning, especially in the material of national movement organizations in class XI MAN Sidoarjo. The research used qualitative methods. The data sources used were observation, interview and documentation. Data were obtained from history teachers, documents, and the implementation of history learning. The results showed that the implementation of the value of nationalism in learning the history of the material of the national movement organization has been implemented according to planning and running well. The value of nationalism that is implemented from the planning and implementation of learning includes discipline, responsibility, religion, respect for the struggle of heroes' services, and love for the country. The obstacles faced by teachers during the learning process are the decline in student behavior, time constraints, lack of learning resources in the form of pictures. The teacher's efforts to overcome the decline in student behavior by instilling morals so that students have a good direction. In addition, the limited time to implement the value of nationalism was overcome by extending it outside of history class hours. Recommendations for future research further explore how the values of nationalism learned in the material of national movement organizations and associated with the local context of Sidoarjo, for example through learning about local figures who have the spirit of struggle or relevant local historical events.